Relationship between facebook use and psychological well-being among secondary school pupils in Malaysia - Naeemi, Seyedeh Somayyeh (2015)
Increasing Facebook usage among adolescents has raised more studies and concerns about psychological well-being. This study investigated the relationships of frequency of Facebook use by purpose and Facebook dependency with psychological well-being in eudaimonic approach. It also examined possible moderation effect of self-efficacy and extrovert/ introvert personality in the relationship between three constructs of frequency of Facebook use by purpose and Facebook dependency with overall psychological well-being. A total of 401 secondary school students aged 13-16 were surveyed by using self-administered questionnaires. Structural equation modeling was used to test hypotheses. The study found a significant positive relationship of friends’ connectivity and organizing event with overall psychological well-being, and a significant negative relationship of information seeking about others and Facebook dependency with overall psychological well-being. The result of study revealed that information seeking about others, friends’ connectivity, organizing events and Facebook dependency predict 34 percent of variance in overall psychological well-being. It also found that extrovert/ introvert personality moderate the relationship of information seeking about others and organizing event with overall psychological well-being, and self-efficacy moderate the relationship of organizing events and overall psychological well-being. In term of theoretical contribution, the study clarified the nature of media influence and reaffirmed how media effect on different aspect of psychological well-being. Specifically, the study clarified the relationship between frequency of Facebook use with eudaimonic well-being of users. In term of practice, the finding can be useful for youth development practitioners,families and subsequently adolescents. Youth developments practitioners through educational workshops can train families by giving appropriate awareness about Facebook usage (based on the information of this study), then families by using this knowledge can monitor their children’s online behavior.